2015
DOI: 10.1248/bpb.b14-00761
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Protocol for the Myocardial Differentiation of Human iPS Cells

Abstract: We have developed a simple protocol for inducing the myocardial differentiation of human induced pluripotent stem (iPS) cells. Human iPS cell-derived embryonic bodies (EBs) were treated with a combination of activin-A, bone morphogenetic protein-4 and wnt-3a for one day in serum-free suspension culture, and were subsequently treated with noggin for three days. Thereafter, the EBs were subjected to adherent culture in media with 5% serum. All EBs were differentiated into spontaneously beating EBs, which were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The mES cells are differentiated spontaneously into cardiomyocytes after the withdrawal of leukemia inhibitory factor (LIF), which helps maintain the pluripotency of the undifferentiated mES cells, from culture medium (Evans and Kaufman, 1981;Martin, 1981;Wobus et al, 1984). We previously developed a simple protocol to differentiate iPS cells into cardiomyocytes within a week by the application of biological substances (Aikawa et al, 2015), which made it possible to carry out the cardiac differentiation assay. In a previous study, the teratogenicity effect of thalidomide had already been predicted (Aikawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mES cells are differentiated spontaneously into cardiomyocytes after the withdrawal of leukemia inhibitory factor (LIF), which helps maintain the pluripotency of the undifferentiated mES cells, from culture medium (Evans and Kaufman, 1981;Martin, 1981;Wobus et al, 1984). We previously developed a simple protocol to differentiate iPS cells into cardiomyocytes within a week by the application of biological substances (Aikawa et al, 2015), which made it possible to carry out the cardiac differentiation assay. In a previous study, the teratogenicity effect of thalidomide had already been predicted (Aikawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental protocol of the iPST in the present study was a partially modified of a previously reported protocol as follows: the drug treatment period was prolonged to 6 days (from 4 days) depending on an cardiac differentiation period, the ReLeSR™ as a cell dissociation reagent was used instead of dispase to equalize the number of cells seeding, and the author's original prediction criteria, established by assay of the mouse cells, was improved to the classification of the type for developmental toxicity as the developmental toxicity prediction model (Aikawa et al, 2014(Aikawa et al, , 2015. In the present study, the iPST was validated internally using various reference drugs.…”
Section: Introductionmentioning
confidence: 99%